Today’s conception of “athlete’s heart” (Fiep Bulletin - online, 2015)
Till now, there were striking differences in the meaning of the expression “athelete’s heart” by different authors. Most of them use this denomination for a more or less enlarged heart of a trained athlete. But often a physician avoids an embarrassing situation by using this expression for any enlarged heart of unknown origin even if the subject have not made any noteworthy effort within the past ten years.